A Questionnaire-Based Survey: Therapist's Response On Emotions Gestures Using Humanoid Robot For Autism - Mohd Azfar, Miskam; Syamimi, Shamsuddin; Hanafiah, Yussof; Ilmi, Mohd Ariffin; Abdul Rahman, Omar (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2015)
This paper is, we used a humanoid robot to physically show emotional poses and conduct a simple guessing game with children. Nine different emotions using the robot's body poses have been developed using Choregraphe. Naturally, we need to approximate as closely as possible natural human behaviour to be done by robot to engaging the children to interact with normal human. Therefore, this study is continuation of our previous study on emotion gestures where we get the therapists response towards module of emotions-based teaching module for children with autism. The role of therapists is to give their main knowledge of autism therapy to bring the right creation of module program using robot.